2021
DOI: 10.4236/msce.2021.98001
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of the Formation Reaction of Polyacid Precursors of Glass-Ionomer Materials

Abstract: The formation of polyacids in a glass-ionomer cement was computationally modeled. The polyacid modelled is an oligomer made up of three molecules: acrylic acid, itaconic acid and an additional molecule that acts as a spacer group between the previous two. Acryloyl and meta-acryloyl derivatives of some amino acids and related molecules such as N-vinyl pyrrolidone and Nvinyl caprolactam were used as spacer groups. Some of these molecules have been previously used experimentally as spacer groups. In this work the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…It examines 15 different polyalkenoic acid formulations which contain acrylic acid, itaconic acid, amino acid derivatives and various spacer molecules to standardize the optimal composition. This is the first computational study that provides insight into the position of polyalkenoic acid and its interactions within the cement forming network J. Gaviria et al 122 Density functional theory (DFT)…”
Section: Ab Initio Molecular Dynamics Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It examines 15 different polyalkenoic acid formulations which contain acrylic acid, itaconic acid, amino acid derivatives and various spacer molecules to standardize the optimal composition. This is the first computational study that provides insight into the position of polyalkenoic acid and its interactions within the cement forming network J. Gaviria et al 122 Density functional theory (DFT)…”
Section: Ab Initio Molecular Dynamics Simulationsmentioning
confidence: 99%
“…Gaviria et al conducted a computational study of polyalkenoic acid formulation in glass-ionomer cement using three different components including acrylic acid and itaconic acid, as well as a spacer molecule. 120 The study demonstrated the behaviour of 15 distinct spacer molecules and optimised the structural arrangement to improve the stability of polyalkenoic acid via the Gaussian 90 computational package using density functional theory. The results demonstrated that in addition to acting as spacer molecules, amino acid derivatives can establish energy interactions with itaconic acid and acrylic acid present in polyalkenoic acid formulation and lead to compaction and energetic stabilisation of the structure.…”
Section: Ab Initio Molecular Dynamics Simulationsmentioning
confidence: 99%
“…This work presents the continuation of the study published by Gaviria [ 14 ] (named as stage 1), where the most stable molecules of some basic structures that make up polyacids were chosen to be evaluated as reagents in obtaining glass-ionomer materials.…”
Section: Introductionmentioning
confidence: 99%